Improving mortality outcomes of Stevens Johnson syndrome/toxic epidermal necrolysis: A regional burns centre experience. Issue 3 (May 2018) - Nizamoglu, M.; Ward, J.A.; Frew, Q.; Gerrish, H.; Martin, N.; Shaw, A.; Barnes, D.; Shelly, O.; Philp, B.; El-Muttardi, N.; Dziewulski, P.
Highlights: Retrospective review of SJS/TEN managed at a regional UK burns centre. We present a management algorithm for SJS/TEN patients. Improved observed versus predicted mortality. Abstract: Introduction: Stevens Johnson Syndrome/toxic epidermal necrolysis (SJS/TEN) are rare, potentially fatal desquamative disorders characterised by large areas of partial thickness skin and mucosal loss. The degree of epidermal detachment that occurs has led to SJS/TEN being described as a burn-like condition. These patients benefit from judicious critical care, early debridement and meticulous wound care. This is best undertaken within a multidisciplinary setting led by clinicians experienced in the management of massive skin loss and its sequelae. In this study, we examined the clinical outcomes of SJS/TEN overlap & TEN patients managed by our regional burns service over a 12-year period. We present our treatment model for other burn centres treating SJS/TEN patients. Methods: A retrospective case review was performed for all patients with a clinical diagnosis of TEN or SJS/TEN overlap admitted to our paediatric and adult burns centre between June 2004 and December 2016. Patient demographics, percentage total body surface area (%TBSA), mucosal involvement, causation, severity of illness score (SCORTEN), length of stay and survival were appraised with appropriate statistical analysis performed using Graph Pad Prism 7.02 Software. Results: During the study period, 42 patients (M26; F: 16) with TEN (n = 32) and SJS/TEN overlap (n = 10) were managed within our burns service. Mean %TBSA of cutaneous involvement was 57% (range 10–100%) and mean length of stay (LOS) was 27 days (range 1–144 days). We observed 4 deaths in our series compared to 16 predicted by SCORTEN giving a standardised mortality ratio (SMR) of 24%. Conclusion: Management in our burns service with an aggressive wound care protocol involving debridement of blistered epidermis and wound closure with synthetic and biological dressings seems to have produced benefits in mortality when compared to predicted outcomes.